Knowledge Evidenced by Prospective Mathematics Teachers when Performing a Task Involving Geometry, Teaching and the Use of Technology - Morales-López, Yuri (2019)
The types of knowledge that prospective mathematics teachers use when faced with tasks involving technology are interesting because this knowledge can be used as a basis for analyzing the relevance of these types of activities when teaching mathematics. This investigation is intended to identify the knowledge evidenced by these prospective teachers when they carry out an activity involving geometry, technology and pedagogy. To do so, a task was designed which was used with 65 trainee teachers, and the Technological Pedagogical Content Knowledge model was used to analyze the information gathered. The results show that prospective teachers make use of knowledge in all of the domains and almost all of the subdomains of the model, confirming that this type of activity triggers these types of knowledge.